Senna siamea (LAM) and its potential for protective forestry (1999)
There is problem of desertification worldwide. It is most prevailing in the northern part of Nigeria where the scanty vegetation cover is being destroyed daily for firewood. Firewood problem has been identified as one of problems contributing to land degradation. There is need to plant suitable species with good calorific (fuel) value which in turn will improve the soil as well as ameliorate the encroachment of desert. Senna siemea wood samples were collected from the University of Ibadan plantation. The fuel value was determined using ballistic bomb calorimeter. Twenty trees of the same age were assessed. The mean fuel value for wood and bark were 22275kj/kg and 20961kj/kg respectively. The highest radial value was found near the pith with mean value of 23312.47kj/kg and the least toward the bark (21299. 26kj/kg). Mean tree height and diameter at breast height were 14.20m and 21.68cm respectively. Based on this performance, Senna siamea is being proposed as a suitable species for reforestation, protective forestry in soil conservation, reclaiming denuded areas and for firewood plantation.